Lichen diversity in geothermal area of Kamojang, Bandung, West Java, Indonesia and its potential for medicines and dyes - JOKO KUSMORO; IIN SUPARTINAH NOER; MUHAMAD FEISAL JATNIKA; RIRIN EKA PERMATASARI; RUHYAT PARTASASMITA (Society for Indonesian Biodiversity, 2018)
Kusmoro J, Noer IS, Jatnika MF, Permatasari RE, Partasasmita R. 2018. Lichen diversity in geothermal area of Kamojang, Bandung, West Java, Indonesia and its potential for medicines and dyes. Biodiversitas 19: 2335-2343. The study of lichens diversity in Kamojang, West Java was conducted by survey in geothermal field area following the line transect 6 km along to the East, North West and south from the Power House of Geothermal Power Plant. The lichen samples were taken from bark, soil, and stone. Lichen identification was done by morphological, anatomy and chemical analysis. Dyes potency of Parmotrema and Usnea test using ammoniac fermentation was done in Plant Taxonomy Laboratory of Department Biology, Faculty of Mathematics and Natural Sciences, University of Padjadjaran. The survey has successfully collected 133 species of lichens, belong to 62 genera and 17 families. Parmeliaceae was found as dominant groups, consisting of 33 species and other co-dominant groups are Graphidaceae and Lobariaceae with 24 species and 8 species, respectively. Most lichens in Kamojang geothermal area belong to Ascomycetes, only one Basidiomycetes such as Dictyonema sericeum (Sw.) which found at Kawah Manuk (Manuk crater) area. The rare species of lichens such as Usnea longissima Ach, was found at Pine forest in Arboretum 6 km south of Powerhouse of Kamojang geothermal. Chemical analysis and literature study for Lichenic acid contains was done and generally, atranorin, usnic acid, barbatic and lecanoric acid was found in lichens samples. Amoniac fermentation result showed that Parmotrema tinctorum produced brownish red, red and purple, which occurred within 1 week to 5 weeks after fermentation. While Usnea produced variety of brown color, which occurred within 5 days up to 4 weeks after fermentation. Lichen species containing some medical properties are Bulbothrix, Cladonia and Usnea. While lichens having dyes properties are Hypogymnia, Lobaria, Peltigera, Usnea, and Parmotrema.